2017
DOI: 10.4103/ijem.ijem_168_17
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on vitamin D level in apparently healthy Indian population and analysis of its associated factors

Abstract: Background:Vitamin D which is involved in the maintenance of bone mineral homeostasis has been found to portray various pleiotropic effects. Although it has been widely accepted that serum 25-hydroxy Vitamin D level above 30 ng/ml is considered optimal for the biological actions of Vitamin D, there is a need to explore the levels of Vitamin D reported among Indians from various regions of the country. Hence, this systematic review aims to appraise the status of Vitamin D levels reported from apparently healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
4
34
0
Order By: Relevance
“…This study also detected the effect size of vitamin D level to be high in the South zone compared to other zones. 24 The average vitamin D levels detected in our study from VDD through VDS becomes comparable to the ranges presented above.…”
Section: Discussionsupporting
confidence: 88%
“…This study also detected the effect size of vitamin D level to be high in the South zone compared to other zones. 24 The average vitamin D levels detected in our study from VDD through VDS becomes comparable to the ranges presented above.…”
Section: Discussionsupporting
confidence: 88%
“…Sun exposure is the major source of vitamin D, as very few naturally occurring food are rich in Vitamin D. This high prevalence despite ample sunshine throughout the year in the country could be possibly explained by the darker skin complexion, sunscreen use, less outdoor activities, lack of food fortification with vitamin D (6,7) . Defining vitamin D deficiency based on international cut off may also play a role in finding high prevalence (21,22). Further studies on clinical significance of this biochemical diagnosis and defining local cut off and diagnostic criteria would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Country-wide studies have reported a high incidence of VDD among healthy individuals belonging to all age groups residing in different regions of India. [11][12][13] In a hospital-based cross-sectional survey among children aged 6 months to 18 years held in a suburban metropolitan area of Chennai in south India, the prevalence of hypovitaminosis D was 62.2%, among whom only 3% had overt rickets. 14 In another crosssectional study of apparently healthy school children aged 5-10 years belonging to Jaipur in western India, 87.5% children were found to have sub-optimal/deficient vitamin D levels.…”
Section: Resultsmentioning
confidence: 99%
“…: [867][868][869][870][871] International Journal of Contemporary Pediatrics | March-April 2019 | Vol 6 | Issue 2 Page 868 adolescents, young adults and elderly people) residing in different regions (northern, southern eastern, western) of India, with the incidence being similar among subjects from rural and urban areas. [11][12][13] In this cross-sectional study, authors examined serum vitamin D status among healthy school children residing in central Kerala.…”
mentioning
confidence: 99%